Quantitative analyses of the distal bipolar electrogram for focal premature ventricular contraction ablation - Sun Young Jeong; Nigel Gupta; Zhilin Qu; Sen Ji (Journal of Arrhythmia, 2025)
Abstract Background Accurate interpretation of the distal bipolar electrogram (bi‐EGM) is essential for successful ablation of idiopathic focal PVC. Sharp, early, and fractionated bi‐EGM is often considered to be near‐field and targeted, but in an empiric fashion rather than by quantitative criteria. Objectives To quantify the distal bi‐EGM with five parameters to elucidate quantitative criteria distinguishing near‐field from far‐field bi‐EGM. Methods The distal bi‐EGM was quantified and analyzed using: half time of activation (t½), slope factor (S, derived by fitting the Boltzmann equation), linear slope (dV/dt), time from onset of bi‐EGM to surface ECG (Ts) and number of deflections (De#). Results Among 41 patients, 26 were ablated successfully and 15 unsuccessfully. t½ and S, defining the sharpness of the activation process, were significantly different between the two groups (3.2 ± 0.3 vs. 5.9 ± 0.6 ms, p < 0.001 and 0.8 ± 0.1 vs. 4.8 ± 2.0, p = 0.01). Ts was earlier in the successful group (35.6 ± 1.3 vs. 25.8 ± 1.6 ms, p < 0.01). dV/dt and De# were not statistically different (0.2 ± 0.04 vs. 0.1 ± 0.02 mV/ms, p = 0.06; and 2.7 ± 0.2 vs. 2.3 ± 0.3, p = 0.22). The 5 parameters showed indifference across anatomic locations. AUCs of ROC curve are >0.8 (t½ 0.85, S 0.85 and Ts 0.87). Conclusion t½, S and Ts are precise in quantifying the sharpness and earliness of distal bi‐EGM; therefore, discriminating the near‐field from far‐field bi‐EGM for guiding successful ablation.